Physical activity patterns in children with cerebral palsy and typically developing peers. (3rd June 2021) - Okur, Eda Ozge; Inal-Ince, Deniz; Saglam, Melda; Vardar-Yagli, Naciye; Arikan, Hulya
ABSTRACT: Objective: To compare physical activity level between children with cerebral palsy and typically developing peers using accelerometer and activity diary. Method: Twenty children with spastic cerebral palsy Level I and II according to Gross Motor Function Classification System, and 20 healthy age- and sex-matched typically developing peers were included. An activity diary was logged, and each child wore an accelerometer for 4 days, 2 weekdays and 2 weekend days. Results: Total and physical activity energy expenditure assessed using either accelerometer or activity diary was markedly lower in children with spastic cerebral palsy compared to typically developing peers. Moderate and vigorous physical activities and daily total energy expenditure assessed using activity diary were significantly lower in children with cerebral palsy than those of typically developing peers ( p < .05). There was a significant relationship between accelerometer and activity diary in total energy expenditure for children with cerebral palsy (r = 0.752, p < .001) and typically developing peers (r = 0.732, p < .001) and a moderate significant relationship in physical activity energy expenditure for children with cerebral palsy (r = 0.463, p = .040). Conclusion: In this study, children with cerebral palsy had lower physical activity levels than their typically developing peers. The activity diary provided detailed information about physical activities and was correlated with accelerometer data. The activity diary could be a valid measure of physical activity levels in children with cerebral palsy.